Treatment of genitourinary syndrome of menopause: the potential effects of intravaginal ultralow-concentration oestriol and intravaginal dehydroepiandrosterone on quality of life and sexual function - La Rosa, Valentina Lucia; Ciebiera, Michał; Lin, Li-Te; Fan, Shangrong; Butticè, Salvatore; Sathyapalan, Thozhukat; Jędra, Robert; Lordelo, Patricia; Favilli, Alessandro (Menopause Review/Przegląd Menopauzalny, 2019)
The climacteric is considered a natural phase in a woman’s aging process and is defined as the period starting from the decline in ovarian activity until after the end of ovarian function. Genitourinary syndrome of menopause (GSM) is commonly observed in menopausal women and is characterised by a collection of symptoms resulting from changes to the internal and external genitalia as well as the lower urinary tract. Several studies have demonstrated the close association between sexual dysfunction and symptoms related to GSM. Many medications, at different doses, have been studied over the years for the treatment of the symptoms of GSM. More specifically, ultralow-dose intravaginal oestriol and intravaginal dehydroepiandrosterone (DHEA) are reported to improve symptoms, signs, and quality of life of women with GSM, and they are safe owing to their specific local effect. While the dosage and the administration of intravaginal DHEA are well defined, the literature on intravaginal oestriol is less uniform: different doses and times of administration are proposed with different possible combinations with other non-pharmacological therapies, although a more standardised treatment may be necessary. The aim of this review is to summarise the available data about the effects of ultralow-concentration oestriol and intravaginal DHEA on the menopause-related symptoms, quality of life, and sexual function of women affected by GSM.